THE EUROPEAN CONSTITUTIONAL ADAPTATION AND THE IMPETUS OF THE ACCESSION PROCESS TO ITS IMPROVEMENT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
In the context of the accession of the Western Balkans to the EU, which geopolitical challenges haverecently pushed to completion, the defence of fundamental European values and the institutional principles,that are their expression, is becoming increasingly urgent. A new commitment has emerged on the part ofthe European Union to reassert its unity and its responsiveness to welcome the new candidates, imposing arevision of the institutional system within which enlargement must take place. The eastward enlargementof 2004-2005, based on conditional rules, imposing respect for democracy and the rule of law, alreadyrevealed that the deepening of the EU's constitutional set-up cannot be separated from the opening of thenegotiations with potential new members. Indeed, the absence of clear rules governing the entry of newStates, which would, for their part, undertake to respect the obligations arising from European law, on theone hand, and the presence of an incomplete apparatus of sanctions for cases of violation of theseobligations, on the other hand, would impede the orderly development of the integration process. As will beseen, reaffirming that respect for fundamental values within the meaning of Article 2 TEU constitutes aprimary, non-negotiable and mandatory obligation, especially at the time of enlargement, is of absoluteimportance, and it is equally important that this obligation be promptly guaranteed by political andjurisdictional remedies of a punitive nature. On the contrary, a disengagement on such issue wouldundermine the credibility of the European project whose historical and ideological significance is based onan identity common to European nations.
Keywords: Fundamental values, crisis, sanctions, enlargement, constitutional reform.